1992
DOI: 10.1524/strm.1992.10.12.163
|View full text |Cite
|
Sign up to set email alerts
|

Test of Fit With the Koziol-Green Model for Random Censorship

Abstract: A model for random censorshlp in which the reliablllty functlon of time censor is a power of the reliabllity function of original data is considered (Koziol-Green model) and a test of fit with this model is suggested. The test is based on an equivalent condition for the Koziol-Green property of reliability functions. This property is equivalent to the equality of certain conditional distributions. A Kolmogorov-Smirnov statistic for the corresponding empirical conditional distribution functions is constructed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
1
4
0
Order By: Relevance
“…The properties of estimators (12) are established from the corresponding properties of estimators (4),(7), (8) and (10). In accordance with results of Cheng [7] under Conditions I we obtain asymptotic unbiasedness of , , , n n n n A A A B % % %…”
Section: Asymptotic Properties Of Estimators Of Survival Functionsupporting
confidence: 77%
See 1 more Smart Citation
“…The properties of estimators (12) are established from the corresponding properties of estimators (4),(7), (8) and (10). In accordance with results of Cheng [7] under Conditions I we obtain asymptotic unbiasedness of , , , n n n n A A A B % % %…”
Section: Asymptotic Properties Of Estimators Of Survival Functionsupporting
confidence: 77%
“…Namely, the estimation of survival, hazard, quantile, mean and percentile residual life, total time on test, Lorenz, density and hazard rate functions is considered, and boot strapping in this model is sketched [8]. Testing the model is also discussed (see, also [10,[12][13][14]). However, it has been pointed out by many authors that the assumptions of PHM are much restrictive.…”
Section: Introductionmentioning
confidence: 99%
“…Testing of the KG assumption is desirable in order to check whether the advantages of proportional hazards can really be used. Tests for the KG assumption itself are available in Cox (1959), Csorgo (1989), Herbst (1992), Henze (1993) and Dauxois and Kirmani (2003).…”
Section: The Sampling Designmentioning
confidence: 99%
“…We continue the works [3] and [4], where Bayesian estimators and above all their asymptotic properties and Bayesian risk are studied. [6] deals with the asymptotic properties of the maximum likelihood estimator, in [5] a test of fit with the Koziol-Green model is given. A review of models and methods of estimation is found in [7].…”
Section: Introductionmentioning
confidence: 99%